2000
DOI: 10.1046/j.1440-1843.2000.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of alveolar surfactant changes with training in humans

Abstract: We conclude that training markedly alters the composition of alveolar surfactant both at rest and with exercise; the physiological significance of these changes remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It has previously been reported that surfactant cholesterol increases rapidly with oleic acidinduced acute lung injury and is elevated in alveolar proteinosis (44). However, alveolar cholesterol also increases rapidly with exercise and these increases are more evident in fit individuals (45). It is known that cholesterol can interfere with the ability of DPPC-containing films to attain high surface pressures on the Langmuir balance, but at low concentrations this sterol has no effect on tensiometric behavior of surfactant on the captive bubble (46).…”
Section: Discussionmentioning
confidence: 94%
“…It has previously been reported that surfactant cholesterol increases rapidly with oleic acidinduced acute lung injury and is elevated in alveolar proteinosis (44). However, alveolar cholesterol also increases rapidly with exercise and these increases are more evident in fit individuals (45). It is known that cholesterol can interfere with the ability of DPPC-containing films to attain high surface pressures on the Langmuir balance, but at low concentrations this sterol has no effect on tensiometric behavior of surfactant on the captive bubble (46).…”
Section: Discussionmentioning
confidence: 94%
“…SP-A protein levels are increased in the serum, plasma and sputum of smokers (Kida et al, 1997;Nomori et al, 1998;Mazur et al, 2011), providing another rationale for the proposed beneficial effects of smoking or nicotine consumption in preventing COVID-19 (Farsalinos et al, 2020a). Furthermore, the composition of surfactant highly significant changes rapidly with exercise in a manner related to fitness and training (Doyle et al, 1994(Doyle et al, , 2000. In line, there is an inverse association between serum SP-D and body mass index (Zhao et al, 2007), and moreover inverse association with human obesity (Sorensen et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Significantly, a clear relationship exists between the subtypes obtained ex vivo and pulmonary physiology. ,,,, First, newborns are devoid of SA at birth, and these accumulate during the first few hours of respiration. , Second, studies with either radiolabelled or stable isotopes in either neonatal or adult lungs demonstrate a metabolic relationship in which the label first incorporates into LA and follows into the SA fraction. , Third, in adulthood, the relative levels of LA and SA are relatively constant, with the lighter subtypes accounting for a third to a half of the surfactant lipid depending on the species. Fourth, under various physiological conditions, including lung injuries, exercise, hyperventilation, and ischemia:reperfusion, the relative proportions of the subtypes change. , Specifically, increased relative amounts of SA are observed in lavage fluid with ARDS …”
Section: What Do Physiological and Pathophysiological Studies Teach U...mentioning
confidence: 99%
“…730 Rapid changes in the disaturated PC:cholesterol ratio have been noted with alterations in total lung volume and the rate of breathing. 108,566,686,731 The source of the increased cholesterol or the manner by which alveolar cholesterol is rapidly decreased are not apparent, although macrophages could be involved. Recent evidence indicates the ABC lipid transporters are important in controlling pulmonary cholesterol homeostasis.…”
Section: Notable Deficiencies In Our Current Appreciation Of Pulmonar...mentioning
confidence: 99%
See 1 more Smart Citation